La empresa transideológica y las relaciones económicas este-oeste-sur - Berríos, Rubén (Estudios Internacionales, 1982)
One of the most surprising developments in the world economy in recent years has been the dramatic expansion of economic relations between centrally planned economies and market economies (developed and underdeveloped). This growing trend in international economic relations has come to be known as the transnationalization of the world economy. This paper provides new observations on the role of transnational companies (from the West and the East) in the economic relations between the East-West-South, offering an overview of the essential characteristics of this triangular relationship, particularly in relation to the commercial exchange, investment, scope and mechanisms in the sale of technology to less developed countries.